Next‐generation sequencing of a family with a high penetrance of monoclonal gammopathies for the identification of candidate risk alleles. Issue 19 (23rd May 2017) - Bolli, Niccolo; Barcella, Matteo; Salvi, Erika; D'Avila, Francesca; Vendramin, Antonio; De Philippis, Chiara; Munshi, Nikhil C.; Avet‐Loiseau, Herve; Campbell, Peter J.; Mussetti, Alberto; Carniti, Cristiana; Maura, Francesco; et al.
Abstract : BACKGROUND: The authors describe a family with a high penetrance of plasma cell dyscrasias, suggesting inheritance of an autosomal dominant risk allele. METHODS: The authors performed whole‐exome sequencing and reported on a combined approach aimed at the identification of causative variants and risk loci, using the wealth of data provided by this approach. RESULTS: The authors identified gene mutations and single‐nucleotide polymorphisms of potential significance, and pinpointed a known risk locus for myeloma as a potential area of transmissible risk in the family. CONCLUSIONS: To the authors' knowledge, the current study is the first to provide a whole‐exome sequencing approach to such cases, and a framework analysis that could be applied to further understanding of the inherited risk of developing plasma cell dyscrasias. Cancer 2017;123:3701–3708. © 2017 American Cancer Society Abstract : The current study describes a framework analysis of germline next‐generation sequencing data that has the potential to identify the genetic basis of a hereditary predisposition toward cancer in a family. Furthermore, the analysis can provide a solid basis for counseling other members of the family.